2011
DOI: 10.1590/s0100-69912011000100009
|View full text |Cite
|
Sign up to set email alerts
|

O etil-2-cianoacrilato como selante após ressecção parcial de ceco em rattus norvegicus albinus

Abstract: Methods: Methods: Methods: Methods: We used 45 male Wistar rats, divided into three equal groups; in all there was performed a partial resection of the cecum. The groups were designated as Group 1: the lesion was treated with application of ethyl-2-cyanoacrylate, Group 2: suture and application of ethyl-2-cyanoacrylate, Group 3: purse-string suture. The animals were monitored postoperatively and half of each group was necropsied 14 days after the procedure, the remaining on the 28 th . They were subjected to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…compounds have been used as complement to conventional sutures. There are studies that show that they are able to create syntheses with no suture in intestines since they do not cause tissue ischemia 6,7 .…”
Section: IImentioning
confidence: 99%
“…compounds have been used as complement to conventional sutures. There are studies that show that they are able to create syntheses with no suture in intestines since they do not cause tissue ischemia 6,7 .…”
Section: IImentioning
confidence: 99%
“…These adhesives have advantages over conventional sutures for the skin and mucous membranes and are indicated for a variety of syntheses such as gingival lesions, skin and mucosa lacerations, with excellent biocompatibility and few secondary tissue reactions. compatible with injuries on the back of rats as used in this research, with higher tension 6 .…”
Section: Discussionmentioning
confidence: 80%
“…Usually, these compounds have been used as complements to conventional sutures, being their use isolated and, when used, presenting questionable results 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there have been experimental studies that have shown the advantages of suture-free intestinal application using tissue adhesive, because tissue adhesives do not impair the tissue perfusion (Weiss and Haj 2001 ; Kanellos et al 2002 ; Faion et al 2011 ). However, there have so far been no reports of cyanoacrylate tissue adhesive use for stoma creation.…”
Section: Introductionmentioning
confidence: 99%